Vertebral Artery Dissection Complicated by Basilar Artery Occlusion - Chia-Yin Kuan; Kun-Long Hung (Elsevier, 2014)
Acute basilar artery occlusion (ABAO) is an infrequent but potentially fatal complication that can cause strokes in both adults and children. Traumatic vertebral artery dissection (VAD) is one of the most common causes of ABAO in young patients. We present a case of an 11-year-old boy with VAD complicated by basilar artery occlusion 2 days after a fight with classmates that caused severe neurological deficits. He did not have any direct head trauma or concomitant risk factors. Clinical symptoms included nausea, vomiting, and rapid alteration of consciousness. Magnetic resonance imaging showed total occlusion of the basilar artery, and angiography confirmed VAD from the third to the fourth segments. A history of such subtle precipitating events should be noted when diagnosing young patients with brainstem strokes. A delay in the diagnosis of ABAO is frequently due to misleading symptoms and signs and the lack of awareness of this rare condition.